Metabolomic Signatures Highlight Fiber-Degrading Bacteroides Species in Mediterranean Diet Response Among Ulcerative Colitis - Natasha Haskey; Jiayu Ye; Jessica Josephson; Maitreyi Raman; Sanjoy Ghosh; Deanna L. Gibson (Gastro Hep Advances)
Background and Aims: The Mediterranean diet pattern (MDP) is associated with health-associated gut microbes and metabolites. However, the impact of the MDP on the fecal metabolome in ulcerative colitis (UC) remains unclear. We characterized the fecal metabolome of patients with UC with high adherence to the MDP compared to the Canadian habitual diet (CHD). Furthermore, we explored potential differences in the fecal metabolome between dietary responders and nonresponders to the MDP. Methods: Utilizing untargeted metabolomics on a subset of fecal samples obtained from a randomized controlled trial, adult patients with quiescent UC underwent a 12-week intervention following either the MDP (n = 8) or CHD (n = 8). Liquid chromatography-tandem mass spectrometry was employed to profile endogenous fecal metabolites, while 16S amplicon sequencing was utilized to profile the fecal microbiota. Results: A total of 701 human metabolites were detected, with 35 exhibiting significant differential expression between the MDP and CHD groups. Noteworthy, folate biosynthesis, sphingolipid biosynthesis, and steroid biosynthesis were identified as major pathways affected. Moreover, microbial analysis showed that individuals with increased levels of the class Bacteroidia (Bacteroides vulgatus [B. vulgatus], B. uniformis, and B. acidifaciens) in their stool at baseline were more likely to respond to the MDP. Conclusion: High adherence to an MDP is associated with beneficial metabolite changes associated with reducing inflammation in UC. In addition, fiber-degrading microbes abundant before dietary intervention played a role in the responsiveness to the MDP. This work lays the groundwork for developing a metabolic signature associated with the MDP to develop personalized nutrition strategies for UC prevention and treatment. ClinicalTrials.gov Number: NCT03053713.